Between Political Tones: Investigating the Impact of Political Orientation on Racial Perception. - Oliveira Zacarias, Daniel; Gabriel Modesto, João (Paideia (0103863X), 2025)
Political polarization is a growing phenomenon that intensifies social divisions, potentially influencing how individuals perceive and categorize others. This study aimed to investigate the impact of information about an individual's political orientation on the racialized social group categorization attributed to them. The hypothesis tested was that political statements (left vs. right) could alter racial perceptions of mixed-race candidates. In Study 1, 576 participants evaluated a male photo, and in Study 2, 400 evaluated a female photo. Participants were exposed to political scenarios and answered questions about political position, racialized categorization, and political identification. The results indicated that mixed-race candidates with left-wing statements are perceived as Blacker. Gender (Study 1) and age (Study 2) influenced this categorization. It is concluded that political orientation impacts racial categorization and warrants further investigation, especially regarding these interactions.